PENGARUH LINGKUNGAN KELUARGA DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI PERTANIAN TERPADU PROVINSI RIAU - Lastari, Dinna; Kartikowati, Sri; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aimed to analyze the influence of family environment and entrepreneurial knowledge on the entrepreneurial interest of vocational high school students. This study uses a quantitative descriptive carried out in SMK Negeri Pertanian Terpadu Provinsi Riau. The population in this study are 400 students. The sampling technique using random sampling technique. The sample consisted of 200 students.The data were collected through a questionnaire and documentation. The data were analyzed by means of the descriptive technique and multiple regression. Results of the data shows that the family environment has partial positive significant effect on entrepreneurial interest for SMK Negeri Pertanian Terpadu Provinsi Riau student. Then entrepreneurial knowledge has partially has no effect on the interest in entrepreneurship SMK Negeri Pertanian Terpadu Provinsi Riau student. Results of the data analysis shows that simultaneously family environment and entrepreneurial knowledge have a positive significant effect on the interest in entrepreneurship of the student of SMK Negeri Pertanian Terpadu Provinsi Riau.Key Words: Family Environment, Entrepreneurial Knowledge, Entrepreneurial Interest.